Detection of firearm discharge residue from skin swabs using trapped ion mobility spectrometry coupled to mass spectrometry. Issue 35 (25th July 2018) - McKenzie-Coe, Alan; Bell, Suzanne; Fernandez-Lima, Francisco
Abstract : In the present work, a novel workflow for the detection of both elemental and organic constituents of the firearm discharge residue from skin swabs was developed using trapped ion mobility spectrometry coupled to mass spectrometry. Abstract : In the present work, a novel workflow for the detection of both elemental and organic constituents of the firearm discharge residue from skin swabs was developed using trapped ion mobility spectrometry coupled to mass spectrometry. The small sample size (<10 μL), high specificity and short analysis time (few min) permits the detection of inorganic residues (IGSR; inorganic gunshot residues) and organic residues (OGSR) from one sample and in a single analysis. The analytical method is based on the simultaneous extraction of inorganic and organic species assisted by the formation organometallic complexes ( e.g., 15–5 crown ethers for the sequestering of metals and nitrate species), followed by fast, post-ionization, high resolution mobility ( R IMS ∼ 150–250) and mass separations ( R MS ∼ 20–40k) with isotopic pattern recognition. The analytical performance is illustrated as a proof of concept for the case of the simultaneous detection of Ba +2, Pb +2, Cu +, K +, NO3 −, diphenylamine (DPA), ethyl centralite (EC) and 2, 4 dinitrotoluene (DNT) in positive and negative nESI-TIMS-MS modes. Candidate structures are proposed and collisional cross sections are reported for all organic and organometallic species of interest.